2014
DOI: 10.1177/1352458514538334
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individuals with multiple sclerosis in an electronic medical record

Abstract: Data within an EMR can be used to accurately identify patients with MS. This study has positive implications for clinicians, researchers and policy makers as it provides the potential to identify cohorts of MS patients in the primary care setting to examine quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Administrative data offer a unique opportunity to study the population-based prevalence of chronic diseases such as MS [19,21,22,23,24,25,26,27,28,29], or Parkinson's disease [30]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative data offer a unique opportunity to study the population-based prevalence of chronic diseases such as MS [19,21,22,23,24,25,26,27,28,29], or Parkinson's disease [30]. …”
Section: Introductionmentioning
confidence: 99%
“…However, administrative data have some limitations: they lack comprehensive clinical data, they do not include some population subgroups, nor those services uncovered by the National Health Service (NHS); moreover, the quality of data is not always perfect. For these reasons, it will be desirable to merge clinical registries and administrative data to obtain a complete view of MS, collecting both clinical and health care information [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Krysko et al . 10 found an EMR-based algorithm to identify multiple sclerosis performed well (91.5% sensitivity and 100% specificity) and could be used as an accurate tool in primary-care settings. Ivers and colleagues found that an EMR-based algorithm accurately identified patients with Ischaemic Heart Disease (72.4% sensitivity and 99.3% specificity) while outperforming other methods of identification.…”
Section: Discussionmentioning
confidence: 94%
“…An EMRALD team physician verified the charts to remove false positives from the study cohort, such as those with only brief runs of AF or those with only transient AF following surgery and follow-up testing that was normal. The methods for developing the search are similar to those used in previous studies [77] and based on previously described patient populations [16]. This search algorithm identified AF patients with one or more of the following components: (1) Recording of AF, including paroxysmal AF, “fibrillation”, and “flutter” in the problem list or history of past health fields of the EMR record [Additional file 3]; (2) electrocardiogram (ECG) and Holter monitor reporting AF; or (3) OAC prescription without clot, thrombosis, embolism, DVT, PE, valve replacement in the problem list, or history of past health fields, in combination with calcium channel blockers (CCB), ß-blockers, or digoxin prescription.…”
Section: Methodsmentioning
confidence: 99%